2019
DOI: 10.1180/mgm.2019.70
|View full text |Cite
|
Sign up to set email alerts
|

Nipalarsite, Ni8Pd3As4, a new platinum-group mineral from the Monchetundra Intrusion, Kola Peninsula, Russia

Abstract: Nipalarsite, Ni8Pd3As4, is a new platinum-group mineral discovered in the sulfide-bearing orthopyroxenite of the Monchetundra layered intrusion, Kola Peninsula, Russia (67°52′22″N, 32°47′60″E). Nipalarsite forms anhedral grains (5–80 µm in size) in intergrowths with sperrylite, kotulskite, hollingworthite, isomertieite, menshikovite, palarstanide, nielsenite and monchetundtraite enclosed in pentlandite, anthophyllite, actinolite and chlorite. Nipalarsite is brittle, has a metallic lustre and a grey streak. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Tomamaeite in Hokkaido is found only as minute particles in Pt-Fe(Cu) alloys (Fig. 7), and its occurrence is common in many localities (e.g., Orsoev et al, 2001;Grokhovskaya et al, 2005Grokhovskaya et al, , 2009Kozlov et al, 2011;Tolstykh et al, 2015;Grokhovskaya et al, 2019;Kuzmin et al, 2020). Based on these occurrences, tomamaeite is thought to occur by decomposition of Pt-Fe(Cu) alloys such as tulameenite, and its counterpart, the Pt-rich phase, should also occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomamaeite in Hokkaido is found only as minute particles in Pt-Fe(Cu) alloys (Fig. 7), and its occurrence is common in many localities (e.g., Orsoev et al, 2001;Grokhovskaya et al, 2005Grokhovskaya et al, , 2009Kozlov et al, 2011;Tolstykh et al, 2015;Grokhovskaya et al, 2019;Kuzmin et al, 2020). Based on these occurrences, tomamaeite is thought to occur by decomposition of Pt-Fe(Cu) alloys such as tulameenite, and its counterpart, the Pt-rich phase, should also occur.…”
Section: Discussionmentioning
confidence: 99%
“…Cu 3 Pt mineral was originally discovered in replacement rims composed of tulameenite on an isoferroplatinum core as a fine inclusion with diameters up to several tens of micrometers (Distler et al, 1986) and was subsequently reported to have similar occurrence in various localities (e.g., Orsoev et al, 2001;Grokhovskaya et al, 2005Grokhovskaya et al, , 2009Kozlov et al, 2011;Tolstykh et al, 2015;Grokhovskaya et al, 2019;Kuzmin et al, 2020). Grigor'eva et al (2018) reported the occurrence of 10 µm intergrowth grains consisting of orcelite, laurite, and Cu 3 Pt mineral in chromitite.…”
Section: Introductionmentioning
confidence: 99%
“…До утверждения минерала фаза состава Cu 3 Pt изредка отмечалась в ассоциациях минералов элементов платиновой группы (ЭПГ) из хромититов и других пород зональных базит-ультрабазитовых комплексов урало-аляскинского типа и в связанных с ними россыпях (Дмитренко и др., 1985;Дистлер и др., 1986;Tolstykh et al, 2002;Козлов и др., 2011, Степанов, 2015. На данный момент достоверно известны следующие проявления томамаэита: береговые и речные россыпи в районе Томамаэ (всего восемь россыпей) (Nishio-Hamane, Saito, 2020;, Гальмоэнанский массив, Камчатка (Власов и др., 2002;Козлов и др., 2011;Tolstykh et al, 2004), Нижнетагильский массив, Средний Урал (Козлов и др., 2011;Tolstykh et al, 2015), массив Вересовый Бор, Средний Урал (Степанов и др., 2020), Красногорский и Матыскенский массивы, Корякское нагорье (Дмитренко и др., 1985;Дистлер и др., 1986;, массив Кондёр, Алданский щит (Рудашевский и др., 1992), массив Наган, Западная Монголия (Агафонов, Леснов, 1997), и Оспинско-Китойский массив, Восточный Саян (Orsoev et al, 2000;Орсоев и др., 2001;Григорьева и др., 2018), Бураковский расслоенный комплекс, Северная Карелия (Гроховская и др., 2005), массив Мончетундра, Кольский полуостров (Гроховская и др., 2005;Grokhovskaya et al, 2019) и массив Желтая Сопка, Северный Урал (Кузьмин и др., 2020).…”
Section: Introductionunclassified